ДОСЯГНЕННЯ МАКСИМУМУ ЕКОНОМІЧНОЇ ЕФЕКТИВНОСТІ РОБОТИ КАСКАДА ГЕС З ВРАХУВАННЯМ ГІДРАВЛИЧНИХ ОБ'ЄМІВ ВОДОСХОВИЩ - Махнитко, А.Е.; Герхард, Я.Х.; Ломан, Т.В.; Варфоломеєва, Р.В.; Обоскалов, В.П.; Колясников, К.С. (Інститут електродинаміки НАН України, Київ, 2016)
At the conditions of market relationships and economic and financial independence of power companies, these are guided by the principle of achieving maximum efficiency in their actions. In the article is considered the problem formulation of HPP cascade operational mode determination, ensuring maximum profit from the sales of the generated electric power at the day-ahead market. Dynamic volumes of reservoirs are taken into account using the lag time between the waves of HPP water flow. The problem solution using the method of statistical modelling is approbated on the example of hypothetical cascade of three HPP. The results of the modelling of cascade operating regime are illustrated graphically. References 5, figures 2, table 1.